Dallas UtErus Transplant Study: Early Outcomes and Complications of Robot-assisted Hysterectomy for Living Uterus Donors. Issue 1 (24th December 2020) - Johannesson, Liza; Koon, E. Colin; Bayer, Johanna; McKenna, Gregory J.; Wall, Anji; Fernandez, Hoylan; Martinez, Eric J.; Gupta, Amar; Ruiz, Richard; Onaca, Nicholas; Testa, Giuliano
Abstract : Background: Uterus transplantation is a treatment for absolute uterine infertility and can be performed with living and deceased donors. Given the safety and increased utilization of robotic assistance with other gynecologic and transplant donor operations, we adopted a robot-assisted approach to donor hysterectomy. This study compared early outcomes and morbidity of the robot-assisted approach to donor hysterectomy with the traditionally performed open approach and addressed whether the robot-assisted approach is safe and offers advantages for the donor. Methods: Our institution has performed 18 living donor hysterectomies for uterus transplantation. This retrospective review compared the last 5 cases utilizing a robot-assisted technique and vaginal extraction of the uterus graft with the first 13 cases performed with an open laparotomy technique. Demographic, intraoperative, and postoperative data were examined. Results: There were no differences between the robot-assisted and the open living donor group with respect to age, body mass index, or gynecological history. Although the median operative time was shorter for the open approach (6.27 versus 10.46 h), the donors' median estimated blood loss, length of hospital stay, and length of sick leave were less with the robot-assisted approach. There was no conversion to open hysterectomy in the robot-assisted cases, and the incidence of complications was similar between the 2 groups. There was no difference in early graft function. Conclusions: These preliminary results show that robot-assisted living donor hysterectomy is feasible and safe for the donors; it allows a faster postoperative recovery and the same early graft function.